Методика визначення інформативних показників, що характеризують функцію статичної рівноваги фахівців екстремальних видів діяльності - Оникієнко, Юрій Юрійович (НТУ "ХПІ", 2017)
Розглядається питання визначення інформативних показників, що характеризують функцію статичної рівноваги. В якості метода дослідження статичної рівноваги використовується модифікований варіант кефалографічної установки. Визначені ключові інформативні показники, що характеризують просторовий динамічний діапазон та особливості коливань тіла відносно осі z, а саме: коефіцієнт, що характеризує зміну вибіркового математичного сподівання rmK ; коефіцієнт, що характеризує зміну вибіркової дисперсії rDK та коефіцієнт, що характеризує зміну вибіркової асиметрії raK . Результати роботи можуть бути використані під час проведення психофізіологічного відбору.

The paper deals with problems of determination of the informative indices, which characterize the function of the human balance (human static equilibrium). The kefalographic method for research of the human static equilibrium is suggested. The kefalographic plant for this method implementation was modified. The informative indices, which characterize the function of the static equilibrium, were determined. As a scientific novelty, the further development of non-invasive study the function of the human static balance (human static equilibrium), which differs from the existing application of the properties of the point camera model, has made it possible to expand the measurement range of the controlled amount and improve the accuracy of the kefalographic reproduction. The suggested criteria were firstly used for selection of the polar explorers worked at the Antarctic station “Academician Vernadsky”. Their application has decreased a time necessary for selection of the polar explores with improved possibilities for extreme activity.
Method of determining the informative indicators with characterizing the function of the static equilibrium for specialist's of extreme types of activities
Keywords: кефалографія; кефалограма; стан психофізиологічний; апарат вестибулярний; kefalography; kefalogram image; psychophysiological state; vestibular apparatus